Comandante Sales 2008: naufrágio e vestígios - Machado, Estéfany Alexandra Menezes (Brasil, 2024)
The main objective of this work was the production of a documentary that addressed the shipwreck of the Comandante Sales boat, which occurred in 2008 in the municipality of Manacapuru, and became the first fluvial case to be brought to trial in the state of Amazonas. To achieve this goal, documentary research was conducted, including interviews with the families of the victims, survivors of the accident, and rescue teams. In addition, newspapers, reports, official documents, photographs, television program videos, and other materials were analyzed (Fonseca, 2002). Exploratory research was also attributed to gather all evidence related to the shipwreck for which there is no knowledge, in order to increase the possibility of conducting a comprehensive investigation into the possible causes of this accident, as well as other similar examples. These tragedies highlight issues such as overcrowding, natural obstacles, and other factors such as lack of preventive education, passenger and cargo overload, lack of proper vessel maintenance, alcohol consumption, and crew inexperience.